Long-Term Symptoms among COVID-19 Survivors in Prospective Cohort Study, Brazil - Bonifácio, Lívia P.; Csizmar, Viviane N.F.; Barbosa-Júnior, Francisco; Pereira, Ana P.S.; Koenigkam-Santos, Marcel; Wada, Danilo T.; Gaspar, Gilberto G.; Carvalho, Felipe S.; Bollela, Valdes R.; Santana, Rodrigo C.; Souza, João P.; Bellissimo-Rodrigues, Fernando (Emerging infectious diseases, 2022)
We conducted a prospective cohort study in a population with diverse ethnic backgrounds from Brazil to assess clinically meaningful symptoms after surviving coronavirus disease. For most of the 175 patients in the study, clinically meaningful symptoms, including fatigue, dyspnea, cough, headache, and muscle weakness, persisted for >120 days after disease onset.